2020
DOI: 10.1038/s41467-020-16016-y
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular electron transfer-dependent anaerobic oxidation of ammonium by anammox bacteria

Abstract: Anaerobic ammonium oxidation (anammox) bacteria contribute significantly to the global nitrogen cycle and play a major role in sustainable wastewater treatment. Anammox bacteria convert ammonium (NH4+) to dinitrogen gas (N2) using intracellular electron acceptors such as nitrite (NO2−) or nitric oxide (NO). However, it is still unknown whether anammox bacteria have extracellular electron transfer (EET) capability with transfer of electrons to insoluble extracellular electron acceptors. Here we show that freshw… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
97
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 234 publications
(101 citation statements)
references
References 65 publications
3
97
1
Order By: Relevance
“…It was stated that HAO enzyme catalyzes the oxidation of NH 2 OH by only three electrons to NO, then an unknown enzyme involves further oxidation reaction for the conversion of NO to NO − 2 . Also, recently it was demonstrated that anammox bacteria oxidized NH + 4 to dinitrogen gas with NH 2 OH as intermediate of the process while transferring electrons to insoluble extracellular electron acceptors such as graphene oxide or electrodes in microbial electrolysis cells (Shaw et al, 2020). Shaw et al (2020) also suggested a potential HAO enzyme in Ca.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It was stated that HAO enzyme catalyzes the oxidation of NH 2 OH by only three electrons to NO, then an unknown enzyme involves further oxidation reaction for the conversion of NO to NO − 2 . Also, recently it was demonstrated that anammox bacteria oxidized NH + 4 to dinitrogen gas with NH 2 OH as intermediate of the process while transferring electrons to insoluble extracellular electron acceptors such as graphene oxide or electrodes in microbial electrolysis cells (Shaw et al, 2020). Shaw et al (2020) also suggested a potential HAO enzyme in Ca.…”
Section: Discussionmentioning
confidence: 99%
“…Also, recently it was demonstrated that anammox bacteria oxidized NH + 4 to dinitrogen gas with NH 2 OH as intermediate of the process while transferring electrons to insoluble extracellular electron acceptors such as graphene oxide or electrodes in microbial electrolysis cells (Shaw et al, 2020). Shaw et al (2020) also suggested a potential HAO enzyme in Ca. Brocadia sinica, an ortholog of the proposed nitrite reductase in Ca.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Electroactive bacteria (EAB) are a unique group of bacteria, which can perform extracellular electron transfer (EET) for anaerobic respiration (Lovley, 2003; Shi et al ., 2016; Logan et al ., 2019). EAB species are ubiquitously distributed across diverse niches and can harness a wide range of terminal electron acceptors (Light et al ., 2018; Costa et al ., 2019; Leu et al ., 2020; Shaw et al ., 2020). They are endowed with the important roles in wastewater treatment and environmental remediation (Rahmani et al ., ), bioenergy harvesting, and geoengineering (Guzman et al ., 2019).…”
Section: Introductionmentioning
confidence: 99%
“…30 However, anaerobic organisms such as acetogens or anammox bacteria do not require oxygen, but instead have evolved to use alternative substrates assimilation and cofactors regeneration strategies to produce energy and biomass, and oxygen impermissible LMs could be applicable for cultivating such microbes. [31][32][33] Despite the advances demonstrating possible processes and products, a better understanding of…”
Section: Introductionmentioning
confidence: 99%